HISTORIC BUILDING APPLICATIONS IN JAKARTA using Macromedia Flash 8.0 - Hilman Adly Maris; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2009)
Scientific writing is about a Historic Building Applications in Jakarta. Thisapplication was created to help users who want to know information about thehistorical development of museums with interesting and interactive view and applyinformation technology emerging today.In scientific writing, the author makes an application using Macromedia Flash 8.0ActionScript 2.0 programming language to facilitate the author in pembutanapplication that displays text, moving images and sound. thus can be expected toattract more users in recognizing existing historic buildings in jakarta.